Effect of the intensity of defoliation in the structure of pasture of Lolium perenne cv Horizon - Saldanha, Sylvia; Boggiano, Pablo; Cadenazzi, Mónica (Agrociencia Uruguay, 2010)
The effect of intensities of grazing applied as forage offers (OF) - 2,0 - 4,5 - 7,0 and 9,5 kg DM/100 kg of animal liveweight on tillers density and dry weight was evaluated from August to November in a Lolium perenne sward. The design was totally at random with two replicates. The relationships between both variables and the OF were lineal in October and November: Tillers density (tillers/m2 )=1821+209 OF (P <0,001; r2 =0,76), Tillers dry weight (mg)=19,3+8,1 OF (P <0,0001; r2 =0,70). No compensatory mechanisms occurred. Grazing intensity affected the persistence of the pasture. In November, 58 plants/m2 got lost for every 1 % decrease in the OF (P <0,0001; r2 =0,84). The OF also affected pasture regrowth. The relationship between tiller weight of the remainder pos-graze and tiller weight of the regrowth for the whole period was significant (P <0,0004; r2 =0,66): Tillers dry weight (mg) pregraze=34,61+0,99 x, for x=weight of tiller of the forage remainder of the previous defoliation. The obtained results reflect the complexity of the processes. Under Uruguay´s conditions the light is not the main factor limiting pasture productivity, while defoliation intensity is an important variable.